The restatement and beyond : the past, present, and future of U.S. foreign relations law - Stephan, Paul B.; Cleveland, Sarah H., 1965- (New York, NY : Oxford University Press, 2020)
This text provides a comprehensive survey of the most significant issues in contemporary U.S. foreign relations law by leading contributors in the field. Reflecting on the recently published Fourth Restatement of the Foreign Relations Law, they review the context and assumptions on which that work relied, critique its analysis and conclusions, and explore topics left out that need research and development.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 16, 2020).
Keywords: United States -- Foreign relations -- Law and legislation